Desenvolvimento de revestimentos epoxídicos luminescentes com baixa molhabilidade a óleos parafínicos - Araujo, Anderson Mansfield Andrade (2012)
The present study aims to develop a luminescent epoxy coating with low interfacial interaction to paraffinic oils and with a lower incidence of voids or bubbles. The proposed development of the coating occurred from an epoxy resin widely used as a coating of pipes for the oil industry. Initially it was added to the epoxy a modifying agent, causing the Epoxy-M, causing the Epoxy-M, which has higher thermal stability, lower interfacial interaction and lower the incidence of bubbles that the Epoxy. After selecting a pigment that meet requirements such as organic nature, good compatibility with epoxy, the fluorescence emission with excitation out of UV, good cost/benefit, it was added to polymer systems. Later heat treatments were performed between 60 and 120°C for periods between ¼ and 6 ho urs, followed by determining the rate of cure, luminescent analysis, interfacial characterization with oil and finally the evaluation of the formation of bubbles. The results show that Heat treatments at lower temperatures for longer periods are shown to be most suitable for the cure of both the systems polymeric, where it is possible to obtain better response photoluminescent and greater rate of crosslinking.